Nilai-Nilai Filosofi Pada Tradisi Midodareni di Desa Bero Jaya Timur Kecamatan Tungkal Jaya Kabupaten Musi Banyuasin Ditinjau dari Aqidah Islam (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2020)
Philosophical Values ​​in the Midodareni Tradition in Bero Jaya Timur Village, Tungkal Jaya District, Musi Banyuasin Regency in the View of Islamic Aqidah. This study is to determine the Midodareni tradition in the perspective of Islamic aqidah and to determine the activities and symbols in the philosophical values ​​of the Midodareni tradition in Bero Jaya Timur Village, Tungkal Jaya District, Musi Banyuasin Regency in terms of Islamic aqidah. This research uses field research with qualitative methods. In this paper, the authors seek information related to the Midodareni tradition, the object of research is the Midodareni tradition of the people of Bero Jaya Timur Village, Tungkal Jaya District, Musi Banyuasin Regency. namely the customary leaders, elders, actors and religious leaders of East Bero Jaya Village and other Bero Jaya Timur Village Communities. And data collection techniques using the method of observation, interviews, and documentation. Data analysis techniques using descriptive qualitative. The results of the study indicate that the Midodareni traditional marriage process has a distinctive procedure. The Midodareni tradition in the village of Bero Jaya Timur uses the ritual of releasing chickens and balangan gantal. Meanwhile, the Midodareni tradition in terms of Islamic aqidah should not be implemented, because there is no underlying shari'a either from the al-Qur'an or the hadith of the Prophet and its rituals contain elements of shirk. The aim is none other than to stem the destruction of religion from the emergence of bid'ah which is clearly prohibited by religion. Because after all, Islam has been perfected for mankind as a straight path to the pleasure of Allah Ta'ala.